2018
DOI: 10.3802/jgo.2018.29.e28
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in progression from endometriosis to ovarian cancer: a cohort study based on medical insurance data

Abstract: ObjectiveThe objective was to identify risk factors that were associated with the progression from endometriosis to ovarian cancer based on medical insurance data.MethodsThe study was performed on a dataset obtained from the National Health Insurance Research Database, which covered all the inpatient claim data from 2000 to 2013 in Taiwan. The International Classification of Diseases (ICD) code 617 was used to screen the dataset for the patients who were admitted to hospital due to endometriosis. They were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The relationship between endometriosis and ovarian cancer has been shown in various studies through various mechanisms. The results of a cohort study showed that, in people with endometrium, aging, living in urban areas, low or high income, depression, pelvic infection, and lack of childbearing increase the risk of ovarian cancer 68. In 1925, Sampson69 proposed a link between endometriosis and ovarian cancer based on the theory of malignant changes of endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between endometriosis and ovarian cancer has been shown in various studies through various mechanisms. The results of a cohort study showed that, in people with endometrium, aging, living in urban areas, low or high income, depression, pelvic infection, and lack of childbearing increase the risk of ovarian cancer 68. In 1925, Sampson69 proposed a link between endometriosis and ovarian cancer based on the theory of malignant changes of endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pathogenesis of endometriosis is not fully clarified. In general, it is widely accepted that endometriosis could be induced by various factors, and pelvic inflammation has been identified as a prerequisite for the occurrence of endometriosis [25]. With the development of transcriptomics, recent studies confirmed the essential role of different subtypes of RNAs in endometriosis, and a set of well-studied RNAs, including mRNAs, lncRNAs, and miRNAs, had been identified as crucial regulators of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed studies tried to elucidate the reasons behind these contradictory results. An evaluation of 200,000 patients showed that higher risk is associated with greater age, pelvic inflammatory problems, and being childless [38]. A retrospective study of malignancy risks in endometriosis found than not only ovarian cancer, but also cervical, breast, and thyroid cancer have higher incidence [39].…”
Section: Ovarian Cancermentioning
confidence: 99%